2017
DOI: 10.1016/j.bmc.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-(2-aminoethyl)-N-benzyloxyphenyl benzamides: New potent Trypanosoma brucei inhibitors

Abstract: A phenotypic screen of a compound library for antiparasitic activity on Trypanosoma brucei, the causative agent of Human African Trypanosomiasis (HAT), led to the identification of N-(2-aminoethyl)-N-phenyl benzamides as a starting point for hit-to-lead medicinal chemistry. Eighty two analogues were prepared, which led to the identification of a set of highly potent N-(2-aminoethyl)-N-benzyloxyphenyl benzamides with the most potent compound 73 having an in vitro EC50 = 0.001 μM. The compounds displayed drug-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The Pathogen Box contained two further antikinetoplastid pyridyl benzamides, 119 (MMV202553) and 120 (MMV688793), both of which are unreported in the literature and appear to conform to many of the SAR parameters described by Ferrins et al . Buckner and co‐workers identified the related phenyl benzamide 121 as a promising nontoxic antitrypanosomal compound with encouraging pharmacokinetic and pharmacodynamic properties . Further optimisation indicated that the inclusion of a 4‐chlorobenzyloxy substituent such as that observed in compound 122 (MMV688371) improved activity.…”
Section: Kinetoplastids (Trypanosomiasis and Leishmaniasis)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Pathogen Box contained two further antikinetoplastid pyridyl benzamides, 119 (MMV202553) and 120 (MMV688793), both of which are unreported in the literature and appear to conform to many of the SAR parameters described by Ferrins et al . Buckner and co‐workers identified the related phenyl benzamide 121 as a promising nontoxic antitrypanosomal compound with encouraging pharmacokinetic and pharmacodynamic properties . Further optimisation indicated that the inclusion of a 4‐chlorobenzyloxy substituent such as that observed in compound 122 (MMV688371) improved activity.…”
Section: Kinetoplastids (Trypanosomiasis and Leishmaniasis)mentioning
confidence: 99%
“…Further optimisation indicated that the inclusion of a 4‐chlorobenzyloxy substituent such as that observed in compound 122 (MMV688371) improved activity. Finally the pyridyl analogue 123 was found to cure 2/3 mice in an acute T. brucei infection model after oral dosing for four days, whilst retaining encouraging pharmacokinetic and pharmacodynamic properties . The Pathogen Box contains the related compound 124 (MMV688798), which is currently unreported in the literature.…”
Section: Kinetoplastids (Trypanosomiasis and Leishmaniasis)mentioning
confidence: 99%
“…For Scaffold 7, it was poor metabolic stability that precluded its further development. Finally, Scaffold 4 was discontinued because of a "static" killing mechanism [17]. This became apparent during in vivo efficacy experiments when administration of the compound resulted in temporary suppression of parasites followed by rebound.…”
Section: Discussionmentioning
confidence: 99%
“…This became apparent during in vivo efficacy experiments when administration of the compound resulted in temporary suppression of parasites followed by rebound. The "static mechanism could be recapitulated in vitro in "washout" experiments [17], which was latter incorporated into our screening routine to avoid repeating the problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation